Thursday, 14 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.5363
|View full text |Cite
|
Sign up to set email alerts
|

OP0147 Aberrant activation of type i interferon system in anti-mda5 dermatomyositis patients

Abstract: BackgroundAnti-melanoma differentiation-associated gene 5 (MDA5) DM patients have an increased risk of interstitial lung disease (ILD), with a potentially fatal course.1 Viral infection has been speculated to be the putative trigger for anti-MDA5 DM.2 3 The molecular pathogenesis remains largely unknown.ObjectivesIn this study, we aimed to explore the role of type I interferon (IFN) system in the pathogenesis of anti-MDA5 DM.MethodsWe studied 20 anti-MDA5 DM patients and compared them with anti- aminoacyl-tRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Allenbach et al also reported the expression of IFN‐stimulated genes was up‐regulated in muscle but significantly lower than classic DM patients, which further supported our foundings 1 . Conversely, the IFN1 signature levels in peripheral blood mononuclear cells were higher of anti‐MDA5 DM patients than that of antibody‐negative DM patients 24 . This discrepancy may be mainly due to differences in tissue or organ susceptibility to the attacks via anti‐MDA5 antibody regulated pathway.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Allenbach et al also reported the expression of IFN‐stimulated genes was up‐regulated in muscle but significantly lower than classic DM patients, which further supported our foundings 1 . Conversely, the IFN1 signature levels in peripheral blood mononuclear cells were higher of anti‐MDA5 DM patients than that of antibody‐negative DM patients 24 . This discrepancy may be mainly due to differences in tissue or organ susceptibility to the attacks via anti‐MDA5 antibody regulated pathway.…”
Section: Discussionsupporting
confidence: 87%
“…IFN appears to play a key role in the pathogenesis of idiopathic inflammatory myopathies, especially in DM 23 . An up‐regulated IFN signature has been observed in skeletal muscle, skin samples, and peripheral blood mononuclear cells of anti‐MDA5 DM 1,24 . Our study showed the components of the IFN1 signaling pathway (MDA5, MAVS, IRF7, and ISG15), were overexpressed at the protein level, suggesting that the MAVS‐IFN1 pathway is broadly involved in the muscle pathology of anti‐MDA5 DM.…”
Section: Discussionmentioning
confidence: 52%
“…In breast cancer, the activation of TLR3 promotes tumor cell death 18 . Specifically, type 1 interferon (IFN) induced by poly(I:C) activates apoptosis in multiple cancer models in mice and humans 19 . Specifically, apoptotic and necrotic cell death are induced by TLR3 stimulation in human colon and lung cancer 20 .…”
Section: Tlrs Play Context-dependent Roles In Tumor Progression and Mmentioning
confidence: 99%